2013
DOI: 10.2147/ndt.s29105
|View full text |Cite
|
Sign up to set email alerts
|

A review of the potential therapeutic role of statins in the treatment of Alzheimer’s disease: current research and opinion

Abstract: Alzheimer’s disease is one of the most prevalent neurodegenerative disorders. However, there is no current treatment, which definitively influences disease progression over a sustained period. Numerous studies linking an increase in serum cholesterol, mainly during midlife, with the pathogenic process of Alzheimer’s disease have been published. Therefore, the role of statins as a therapy in this disorder may be of great interest. The aim of the present review is to summarize of the role of statins in the treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 104 publications
(104 reference statements)
0
2
0
Order By: Relevance
“…Woods et al [14] suggested that disturbances in the cholesterol system may be a significant factor in the development of psychiatric disorders such as schizophrenia, autistic spectrum disorders and depression as well as AD. The mechanism through which serum cholesterol affects brain cholesterol and brain pathology is unclear at this time [15, 16]. It has been argued that high cholesterol triggers an inflammatory cascade that influences amyloid beta production [17].…”
Section: Introductionmentioning
confidence: 99%
“…Woods et al [14] suggested that disturbances in the cholesterol system may be a significant factor in the development of psychiatric disorders such as schizophrenia, autistic spectrum disorders and depression as well as AD. The mechanism through which serum cholesterol affects brain cholesterol and brain pathology is unclear at this time [15, 16]. It has been argued that high cholesterol triggers an inflammatory cascade that influences amyloid beta production [17].…”
Section: Introductionmentioning
confidence: 99%
“…These cardiovascular risk factors share common pathophysiologic mechanisms of neural-vascular interactions or coupling through which cerebral atherosclerosis, cerebral small vessel disease, disruption of the blood brain barrier, and brain hypoperfusion may occur, leading to neuronal damage or dysfunction [12, 26]. Furthermore, hypertension and hypercholesterolemia may affect brain amyloid-Beta (Aβ) and tau clearance through brain lipid homeostasis and blood flow regulation, further increasing AD risk [2730]. …”
Section: Introductionmentioning
confidence: 99%